Mechanism Design and Simulation Analysis of Hybrid Serial-Parallel Underwater Dredging Manipulator - Yin XIA; Wenbin SU; Qiao HU; Jian ZHANG; Lin SHI (水下无人系统学报)
In recent years, underwater robots have emerged as a novel solution for the removal of sediments at the bottom of reservoirs, with underwater manipulators being the primary tool for dredging operations. To address issues faced by serial manipulators, such as low structural stiffness and poor reliability, a hybrid serial-parallel underwater manipulator was designed, integrating serial and parallel manipulator mechanisms. By using screw theory, a hybrid mechanism and the manipulator structure were designed. A finite element analysis(FEA) software was then used for strength verification and static stiffness simulation analysis. The results indicate that the hybrid serialiparallel manipulator has higher structural stiffness than serial manipulators. The result can provide theoretical and technical support for optimizing underwater manipulator design.